Organization and Management / A Systems and Contingency Approach: Fourth Edition - Kast E. Fremont; Rosenzweig E. James (Mcgraw Hill Book Company, 1985)
Preface, Conceptual Foundations, Evolution of Organization and Management Theory, Environment and Social Responsibility and Goals, Technology and Structure, The Phychosocial System, The Managerial System, Comparative Analysis, Change and Challenge and the Future, Bibliography, Epilogue, Name and Subject Index.
Preface, Conceptual Foundations, Evolution of Organization and Management Theory, Environment and Social Responsibility and Goals, Technology and Structure, The Phychosocial System, The Managerial System, Comparative Analysis, Change and Challenge and the Future, Bibliography, Epilogue, Name and Subject Index.